2003
DOI: 10.1088/0953-8984/15/50/002
|View full text |Cite
|
Sign up to set email alerts
|

Lattice thermal conductivity in superlattices: molecular dynamics calculations with a heat reservoir method

Abstract: We report on a molecular dynamics study of the cross-plane lattice thermal conductivity in GaAs/AlAs superlattices. The layers of the superlattice are modelled by a three-dimensional face centred cubic lattice with cubic anharmonicity, and with atomic scale roughness at the interfaces. We perform the simulation of heat flow for a section of a superlattice with high-and lowtemperature thermal reservoirs attached to opposite ends. The calculation reproduces qualitatively the features observed experimentally, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 37 publications
6
37
2
Order By: Relevance
“…The coverage factor of 1% exhibits the minimum in thermal conductivity as the smooth interfaces. For coverage factor of 10% and 50% the minimum dissapears and the results confirm previous theoretical observations (Daly et al 2002, Imamura et al 2003, while the two defect concentrations do not influence the thermal conductivity. For height of roughness of 2MLs, the thermal conductivity is higher than for smooth interfaces and exhibits a maximum for a 8 0 .…”
Section: Modelling Rough Interfaces For the Gaas/alas Superlatticessupporting
confidence: 88%
See 1 more Smart Citation
“…The coverage factor of 1% exhibits the minimum in thermal conductivity as the smooth interfaces. For coverage factor of 10% and 50% the minimum dissapears and the results confirm previous theoretical observations (Daly et al 2002, Imamura et al 2003, while the two defect concentrations do not influence the thermal conductivity. For height of roughness of 2MLs, the thermal conductivity is higher than for smooth interfaces and exhibits a maximum for a 8 0 .…”
Section: Modelling Rough Interfaces For the Gaas/alas Superlatticessupporting
confidence: 88%
“…Simulations of the thermal conductivity of superlattices as a function of their period exhibit a minimum for period around 8 to 10 monolayers (Daly et al 2002, Imamura et al 2003, Chen 2005b, but this minimum is not observed in experimental measurements (Capinski et al 1999). The quality of the interfaces might be the reason to explain this discrepancy.…”
Section: Thermal Conductivity Predictions For Gaas/alas Superlatticesmentioning
confidence: 95%
“…The predicted minimum in cross-plane thermal conductivity as a function of period length 6,7,9,11,38,55 has been attributed to a transition of thermal transport dominated by superlattice phonons in shortperiod superlattices to thermal transport dominated by bulklike phonons in longer-period superlattices. 56,57 A thicknessdependent thermal conductivity of finite-size GaAs/AlAs superlattices measured experimentally was explained in terms of ballistic superlattice phonons.…”
Section: Superlattice Phononsmentioning
confidence: 97%
“…Previous MD studies used the equilibrium Green-Kubo (GK) 6 technique, the nonequilibrium direct method, [6][7][8][9][10] or imposed a spatial temperature perturbation and monitored the relaxation to equilibrium 11,12 to predict thermal conductivity. Bottom-up studies using the BTE relied upon the validity of bulk phonon properties in each layer 13,14 and approximations for the specularity and conductance of the internal interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, MD simulations have been applied to calculate thermal conductivity of superlattices [16][17][18][19][20] . In particular, Termentzidis et al 17 explored the cross-plane conductivity of superlattices with a variety of interface conformations, similar to part of the current study.…”
mentioning
confidence: 99%